1999
DOI: 10.2307/177239
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Survival in Five Populations of Ungulates: Evidence of Senescence

Abstract: Methodological problems in describing patterns of senescence in wild populations have until recently impeded progress in understanding the evolution of a process that decreases individual fitness. We investigated age-and sex-specific survival in five populations of three species of ungulates (roe deer, Capreolus capreolus; bighorn sheep, Ovis canadensis; and isard, Rupicapra pyrenaica), using recent statistical developments of capture-mark-recapture models and long-term (12 to 22 yr) data on marked individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
126
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 57 publications
(105 reference statements)
10
126
0
Order By: Relevance
“…We found that age was the only covariate included in top models with a significant relationship to survival. We found a weak negative relationship between age and survival, which was consistent with age-specific variation in survival found in other ungulate populations (Loison et al 1999;Gaillard et al 2000;Festa-Bianchet et al 2003). A negative relationship between survival and age in the Fort Riley population could be due to hunters avoiding harvesting a calf or yearling, and thereby increasing the mortality risk for adult female elk in older age-classes (Wright et al 2006).…”
Section: Discussionsupporting
confidence: 87%
“…We found that age was the only covariate included in top models with a significant relationship to survival. We found a weak negative relationship between age and survival, which was consistent with age-specific variation in survival found in other ungulate populations (Loison et al 1999;Gaillard et al 2000;Festa-Bianchet et al 2003). A negative relationship between survival and age in the Fort Riley population could be due to hunters avoiding harvesting a calf or yearling, and thereby increasing the mortality risk for adult female elk in older age-classes (Wright et al 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Compared to the metaanalysis technique of Promislow (1991) and the large-scale targeted data collection of studies such as Loison et al (1999), a mortality structure may be estimated for more species, using data that are already collected. Compared with the use of MRLs to estimate population mortality parameters, our technique gives a direct estimate of the complete mortality curve, rather than estimating a single parameter of it.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have built databases of mortality structures for multiple species (e.g., Promislow 1991, Loison et al 1999. However, these analyses have generally considered only a limited number of species for which the authors have been able to access high-cost population actuarial datasets, many of which have used transversal life-table approaches, and so relied on assumptions such as zero population growth in order to estimate mortality structure.…”
Section: Introductionmentioning
confidence: 99%
“…In age-structured populations, the contribution of an individual to future generations (reproductive value) depends on age-specific transitions among different phenotypic categories affecting their fecundity and survival (Caughley, 1966;. For instance, natural mortality rates in large ungulates are typically low for prime aged adults, and higher for young and old individuals (Gaillard et al, 1998;Loison et al, 1999). Exploited populations will have harvest mortality interfering with natural mortality, changing the distribution of reproductive values by affecting age classes differently (Langvatn and Loison, 1999;Solberg et al, 2000;Engen et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%